Code-Switching in Bilingual Malaysian Polytechnic Settings (Borneo Engineering & Advanced Multidisciplinary International Journal, 2024)
In a bilingual Malaysian polytechnic setting, this research investigates the phenomenon of code-switching. Changing between two or more languages when communicating is a common activity in a variety of linguistic circumstances. In Malaysian polytechnics, multiple languages are spoken, hence code-switching is frequently seen in daily interactions. The goal of this study is to learn how polytechnic students perceive the use of code-switching in English language instruction and to determine how frequently it occurs in their speech. The study investigates the impact of code-switching methods on language learners' capacity to learn a second language. This quantitative study used a Google Form link to obtain the questionnaire that served as the instrument. The data shows that students positively view the practice of switching between languages, particularly during verbal presentations, as it aids in improving both communication and language acquisition. The findings also suggest that students actively use code-switching as a method to enhance learning, rather than merely as a solution for not knowing certain words. Additionally, code-switching is found to offer psychological advantages, such as boosting students' comfort and confidence levels during their presentations. The study highlights the effects of language mixing on educational outcomes, offering guidance for teachers and decision-makers. It seeks to refine language education strategies, fostering a more inclusive and effective learning environment in Malaysian polytechnics by exploring the nuances of bilingual communication.